A Comparison of Prediction of Adverse Perinatal Outcomes between Hadlock and INTERGROWTH-21st Standards at the Third Trimester. (9th January 2019) - Zhu, Chen; Ren, Yun-Yun; Wu, Jiang-Nan; Zhou, Qiong-Jie
Abstract : Little is known about the clinical value of the Hadlock and INTERGROWTH-21 s t EFW standards for predicting adverse perinatal outcomes (APOs) in the third trimester. The purpose of this study was to study the association between low estimated fetal weight percentile (EFWc) in the third trimester and the risk of APOs and compare predictions of APOs between Hadlock and INTERGROWTH-21 s t EFW standards. A prospective cohort of 690 singleton pregnancies with ultrasonography performed in the third trimester between March 2015 and March 2016 in China was conducted. EFW and the corresponding EFWc were measured using the Hadlock and INTERGROWTH-21 s t standards, respectively. Cox proportional hazard models were used to assess the relationship between low EFWc (i.e., <5 percentile, P5) and the risk of APOs. Compared with fetuses with ≥P5 of the EFWc, fetuses with <P5 of the EFWc were much more likely to have an APO, with adjusted hazard ratios of 35.0 (95% confidence interval, 13.9-88.5) and 17.5 (7.7-39.6) for the Hadlock and INTERGROWTH standards, respectively. The Hadlock-EFWc had a higher predictive accuracy for APOs than the INTERGROWTH-EFWc, with area under the receiver operating characteristic curve of 0.94 (0.92-0.95) and 0.90 (0.87-0.92), respectively (P=0.007). The cutoff value for the INTERGROWTH-EFWc was percentile 11.61 with a sensitivity and specificity of 87.9% and 80.5%, respectively. For the Hadlock-EFWc, the corresponding sensitivity and specificity were 93.9% and 81.2%, with a cutoff value of percentile 8.65. Fetuses with low EFWc (i.e., <P5) were associated with an increased risk of APOs. APOs were more accurately predicted when EFWc was measured by the Hadlock standard than by the INTERGROWTH-21 s t standard.